Pengaruh Penerapan Good Manufacturing Practices (GMP) Dan Penyusunan Sanitasi Standar Operasional Prosedur (SSOP) terhadap Proses Pengolahan Cumi Beku yang Dimoderasi oleh Sistem Hazard Analysis Critical Control Point (HACCP) pada PT. Sanjaya Internasional Fishery - Ari Soeti Yani; Riana Wulan Safitri (Jurnal EBI, 2021)
This Study aims to determine the effect of the application of Good Manucturing Practices (GMP) and the preparation of Sanitation Standard Operational Procedure (SSOP) on the processing of frozen squid, and determine the effect of the Hazard Analysis Critical Control Point (HACCP) system as a moderating variable. The results of the research that love been carried out show the influence of the implementation of Good Manufacturing Practices (GMP), preparation of Sanitasi Standard Operational Procedure (SSOP) and Hazard Analysis Critical Control Point (HACCP) on the processing frozen squid. However, moderating the Hazard Analysis Critical Control Point (HACCP) is not able to moderate the Good Manufacturing Practices (GMP) and Sanitation Standard Operational Procedure of the frozen squid processing. From this research, it is explained one of the effects is that there are still irregularities in craying out the application of Good Manufacturing Practices (GMP), Sanitation Standard Operational Procedure (SSOP) and Hazard Analysis Critical Control Point (HAACP) to the frozen squid processing.